Peran Guru Dalam Meningkatkan Kedisiplinan Beribadah Anak Usia Dini Di Ra Perwanida Dusun Pucangombo Kecamatan Tegalombo Kabupaten Pacitan - Nafiah, Siti; Muafiah, Evi (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2020)
Abstract: The objectives of this study are (1) to describe the discipline profile of early childhood worship in RA Perwanida, Pucangombo Hamlet, Tegalombo Pacitan; (2) to describe the role of the teacher as a guide in improving the discipline of early childhood worship at RA Perwanida, Pucangombo Hamlet, Tegalombo Pacitan; (3) to describe the teacher's role as a supervisor in improving the discipline of early childhood worship in RA Perwanida, Pucangombo Hamlet, Tegalombo Pacitan. This study uses a qualitative approach to the type of case study research. The results of this study are: (1) Discipline profile for children of age in RA Perwanida Pucangombo Hamlet Tegalombo Pacitan in general is included in the category of lack of discipline. (2) The role of the teacher as a guide, the teacher collaborates with parents of parents to take part in implementing / implementing regulations has been determined by the school institution in the sense that parents should support the child. 3) The role of the teacher as a supervisior, being a model / example in applying the discipline of worship to early childhood continuously, the teacher provides supervision